Arahan Lokasi Kantor Resort Pengelolaan pada Seksi Pengelolaan Taman Nasional Wilayah I Kopeng Balai Taman Nasional Gunung Merbabu - Sulaksono, Nurpana (Magister Pembangunan Wilayah dan Kota,Undip, 2012)
Taman Nasional Gunung Merbabu (Mount Merbabu National Park) is facing increasing environmental threats coming from several illegal activities such as logging, mining, and also grazing and cultivation. To ensure effective management, the National Park is divided into areas of management identified as resorts. Therefore it is important that the resort offices are established on optimum locations, meeting the optimum criteria (1) requiring minimum cost in reaching prone and vulnerable areas, as well as government facilities, (2) situated in proximity to settlements for security reasons, and (3) not located in areas prone to landslides and other ground movements. The study aims to to determine the optimum location for resort offices in SPTN Region I Kopeng of the National Park. The study completed two analyses. Firstly the study completed locational analysis identifying areas within the National Park’s Selo and Ampel resort meeting the criteria (1) prone to security threats, (2) prone to damage, and (3) prone to natutal disasters. Secondly the study determined the optimum location for Solo and Ampel resort office, meeting the optimum criteria. Analyses concluded that Samiran village is the optimum location to establish the office in Selo resort, while Sampetan village is optimum for Ampel resort.